Peritional Tuberculosis in Young Age Lady Miicking Gynecology Malignancy: a Case Report - Sari, Lusi Jelita; Antonius, Puja Agung; Muhammad, Syamel (Fakultas Kedokteran Universitas Andalas, 2024)
Background : Peritoneal tuberculosis is one of the most challenging forms of extrapulmonary tuberculosis to diagnose. Extrapulmonary TB is very difficult to diagnose because of its non-specific signs and symptoms, thus it sometimes leads to a diagnosis of gynaecological malignancy such as advanced ovarian carcinoma. Case Report : A teenage girl, 12 years old, with a chief complaint of intermittent abdominal pain since the last 1 month. There was no history of an enlarged abdomen, fever and weight loss. Ultrasound examination revealed an irregular adnexal mass suggesting an ovarian malignancy with other possibilities of an infectious process. Diagnostic laparoscopy and peritoneal biopsy were performed on the patient. Intraoperatively, multiple friable nodular-mylar peritoneal masses with abdominopelvic attachments and fibrin fibres and white vesicles were found on the entire surface of the genitalia, peritoneum, and intestines. A mass biopsy was performed with histopathological results showing peritoneal tuberculosis. Currently, the patient is undergoing anti-tuberculosis drugs (OAT) treatment. Discussion : The diagnosis of this disease is difficult to establish. Symptoms are highly variable and non-specific and can lead to the wrong tumour pathology. The clinical characteristics are dominated by changes in general condition, abdominal pain and transit disorders, as well as masses (20 to 25%). The gold standard for definitive PTB diagnosis remains laparoscopy with peritoneal biopsy and subsequent pathological or microbiological confirmation. Yellow/white nodules in the peritoneum observed on the patient's laparoscopic images are the hallmark of wet peritoneal TB. Omental thickening and abdominal cocoon with matted small bowel are other classic laparoscopic findings for peritoneal TB. Conclusion: PTB has similar characteristics to peritoneal carcinoma, which makes diagnosis difficult for clinicians. Early and correct diagnosis of PT